Isolated very low QRS voltage predicts response to tilt‐table testing in patients with neurally mediated syncope. Issue 12 (18th October 2019) - Blendea, Dan; McPherson, Craig A.; Pop, Sorin; Anton, Florin P.; Crisan, Sorin; Ruskin, Jeremy N.
Abstract: Background: A number of patients with neurally mediated syncope (NMS) have isolated QRS complexes of very low voltage (≤0.3 mV) in the frontal plane leads on the 12‐lead electrocardiogram (ECG). Hypothesis: The aim of this study was to assess the importance of QRS voltage in predicting response to tilt‐table testing (TTT) in patients with suspected NMS. Methods: We included 216 patients (age: 49 ± 20 years, 103 men) with suspected NMS who had either a positive or negative response to TTT ( n = 91 TTT+, and n = 125 TTT−). The QRS voltage was measured in mV on 12‐lead ECGs performed within 3 days of the TTT. The lowest QRS voltage (QRSmin), as well as the voltage in each of the 12 leads was also determined. Results: Very low voltage (QRSmin ≤ 0.3 mV) in the frontal leads was significantly more prevalent in the TTT+ group than in the TTT− group (74 vs 22%, respectively; P < .001). Patients in the TTT+ group had significantly lower QRSmin when compared to patients in the TTT− group. QRSmin predicted a positive tilt‐table test in a multivariate model that also included patient gender, height, history of presyncope, QRS duration, and left ventricular end‐diastolic diameter indexed to height. ROC analysis showed that QRSmin of ≥0.3 mV discriminated between TTT+ and TTT− patients with a sensitivity of 78% and specificity of 68%. Conclusion: Isolated very low QRS voltage in the frontal leads predicts a positive response to TTT in patients with suspected NMS.